Propaganda, Social Media, and Political Participation: Quantitative Analysis of The Influence of Propaganda #2019gantipresiden on Outcomes and Levels of Political Participation of National Voters in The 2019 Presidential Elections - Iding Rosyidin; Bambang Ruswandi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
In politics, propaganda is often used, for example, during general elections. Among the propaganda media that can be used is social media such as Twitter. During the 2019 Indonesian presidential election, one of the supporters of the presidential candidate pair carried out propaganda, namely the #2019gantipresiden tweet. From a propaganda perspective, this hashtag can be categorized as the bandwagon type of propaganda (Shabo, 2008), a technique that asks audiences to follow propagandist ideas. This study aims to determine the influence of #2019gantipresiden tweets on the results and participation rates in the 2019 Presidential Election. The data used in this study are tweets with the hashtag #2019gantipresiden spread across 34 provinces in Indonesia. Data was collected over three months, namely May, June, and July 2018, when this hashtag was first launched. In addition, data from the results of the 2019 Presidential Election were obtained from the KPU. The data analysis results show a significant relationship between the number of #2019gantipresiden tweets and the Jokowi-Ma'ruf vote. However, this relationship becomes insignificant when including Prabowo-Sandi's vote acquisition as a control variable and has the opportunity to reduce the vote gain obtained by the Jokowi-Ma'ruf pair. This result is inversely proportional to the relationship between the number of #2019gantipresiden tweets and Prabowo-Sandi's vote gain, where the relationship between the two remains significant whether controlled by Jokowo-Ma'ruf vote gain or not. The appearance of the #2019gantipresiden tweet also triggered public participation in the 2019 presidential election by giving it an influence of 31.4%.